FACTORS CAUSING DIFFICULTIES IN PRACTICING COMMUNICATIVE LANGUAGE TEACHING - Uswatun Qoyyimah (Unipdu Jombang, 2009)
Uswatun Qoyyimah University of Pesantren Tinggi Darul Ulum Jombang Usqyim@yahoo.com Abstract This article discusses about the implementation of Communicative Language Teaching (CLT) approach in English as a Foreign Language (EFL) context. Some believe CLT is a suitable approach to improve student’s communication. However, this article argues that the approach is problematic for non-native English speaking teachers in EFL context. There are several factors causing Communicative Language Teaching less appropriate to implement in this situation. The problems include the facts that teachers are struggling to adapt with the English since this language is not their first or second language, and the concept of CLT remains broad, so that teachers need to have guideline for implementing it in the classroom practice. key word: communicative language teaching (CLT) Abstrak Artikel ini membahas tentang pengajaran bahasa yang komunikatif (Communicative Language Teaching). Banyak pendapat menganggap pendekatan ini sebagai jawaban atas masalah yang berkaitan dengan kemampuan komunikasi pelajar. Bagaimanapun, pengajaran komunikatif bahasa merupakan masalah bagi guru mata kuliah speaking yang bukan berlatar belakang bahasa Inggris. Mereka berpendapat bahwa konsep tidak bisa didapat serta tidak ada kejelasan bagaimana menjalankannya. Di samping itu tantangan untuk dihadapi ketika kemampuan bahasa yang dikuasai rendah. Artikel ini membahas faktor- faktor yang menyebabkan Communicative Language Teaching (CLT) sulit diaplikasikan. kata kunci: communicative language teaching (CLT)